Faktor-Faktor Yang Mempengaruhi Kepatuhan Ibu Hamil Mengkonsumsi Tablet Zat Besi (Fe) Di Wilayah Kerja Puskesmas Tirtajaya Kecamatan Bajuin Tahun 2018 - Nirma Yunita; Salasiah Supiyati; Eka Isdiana (HB PRESS, 2018)
Maternal mortality rate is still high because of anemia during pregnancy. The success of a program providing iron tablet (Fe) made by the government to combat anemia is strongly influenced by the compliance of pregnant women in consuming iron tablet (Fe) but there are still pregnant women who are poorly compliant because do not understand the benefits of iron tablet (Fe), lazy to consume can nausea, and forgotten. This study aims to determine Factors Affecting Compliance of Pregnant Women Consuming Iron Tablet (Fe) in Working Area of ​​Tirtajaya Public Health Sub-District Bajuin Year 2018. This research used an analytical method with Cross Sectional design. This study was conducted on 73 pregnant women respondents. Based on the results of research from several variables using Chi-Square was shown that knowledge obtained p value = 0,000, motivation obtained p value = 0,000, family support obtained p value = 0.003, Antenatal Care obtained p value = 0.011, and other effects obtained value p = 0.001 which means there is a significant relationship with the comformity of pregnant women to consume iron tablet (Fe) at ​​Puskesmas Tirtajaya Kecamatan Bajuin in 2018. Based on the conclusion, we suggested to pregnant women can improve the conformity to consume iron tablet (Fe), and puskesmas can improve effectiveness in handling the problem of anemia, for educational institutions can improve the quality of midwifery services, for further research as a reference for researchers to find other variables about iron tablet (Fe).